HUMAN RESOURCE MANAGEMENT IN THE SAMAPTA FUNCTION OF THE SOUTH LAMPUNG POLICE TO CREATE A SAFE AND CONTROLLED SITUATION IN THE SOUTH LAMPUNG POLICE AREA - Humaeni, Ali; Barusman, Tina Miniawati Virgawenda; Barusman, Andala Rama Putra (Program Studi Magister Manajemen, 2025)
This study aims to analyze human resource management in the Samapta function of the South Lampung Police in realizing a safe and controlled public security and order situation. The focus of the study is directed at the efforts of Samapta human resource management in suppressing minor crimes that have the potential to develop into larger crimes, such as the distribution of alcoholic beverages, motorcycle gang activities, disturbances due to single organ entertainment, and the presence of dimly lit cafes in the South Lampung Regency area. The research method used was a qualitative approach with a descriptive type of research. Data collection techniques were carried out through in-depth interviews, observation, and documentation of informants directly related to the Samapta function of the South Lampung Police. Data analysis was carried out interactively through the stages of data reduction, data presentation, and drawing conclusions, with the aim of obtaining a comprehensive picture of the implementation of human resource management in the Samapta function. The results of the study indicate that human resource management in the Samapta function of the South Lampung Police has not been running optimally. This is evident from the limited number and quality of personnel, the uneven distribution of training and development of member capabilities, and limited supporting facilities and infrastructure. Nevertheless, strategic efforts have been made, such as increasing dialogic patrols, rapid responses to public order disturbances, and community involvement in maintaining environmental security. The implementation of human resource development through training, task arrangement, and strengthening coordination has been proven to contribute to increasing the effectiveness of Samapta's function in maintaining a conducive security situation. The conclusion of this study confirms that planned, sustainable, and field-based human resource management is a key factor in optimizing the function of Samapta. Therefore, it is recommended that the South Lampung Police improve the quality and quantity of Samapta personnel, strengthen training and competency development programs, and optimize the use of technology and supporting facilities to prevent and mitigate security disturbances more effectively